The juvenile justice system: delinquency, processing, and the law - Merlo, Alida V. (Pearson, 2016)
An overview of juvenile justice in the United States -- The history of juvenile justice and origins of the juvenile court -- Theories of delinquency and intervention programs -- The legal rights of juveniles -- Juveniles and the police -- Intake and preadjudicatory processing -- Prosecutorial decision making in juvenile justice -- Classification and preliminary treatment : waivers and other alternatives -- The adjudicatory process : dispositional alternatives -- Nominal sanctions : warnings, diversion, and alternative dispute resolution -- Juvenile probation and community-based corrections -- Juvenile corrections : custodial sanctions and aftercare